Pengaruh Work-Family Conflict terhadap Subjective Well-Being pada Single Parent - Aqila Dwi Ananda Ramadhani; Anna Rozana (Bandung Conference Series: Psychology Science, 2022)
Abstract. The conflict that is felt by single parents occurs because they are responsible for themselves to fulfill the demands of roles in work and family simultaneously, which are usually carried out by husband and wife so that single parents who work are vulnerable to experience work-family conflict and will have an impact on subjective his well-being. This study aims to determine the effect of work-family conflict on subjective well-being in single parents in the city of Bandung. This research is a non-experimental quantitative research. The subjects in this study were 100 single parents who worked in the city of Bandung. Data analysis used Partial Least Square – Structural Equation Modeling (PLS SEM). The measuring instrument used for work-family conflict is the work-family conflict scale from Carlson, Kacmar, & William (2000) which has been adapted and translated by Indah Soca Kuntari, M.Psi, Psychologist (2015). The measuring instrument used for subjective well-being consists of two measuring instruments, namely, SWLS compiled by Diener, Emmons, Larsen & Griffin (1985) and SPANE compiled by Ed Diener (2009), both of which have been adapted and translated by Ratri (2019). The results showed that there was a negative effect of work-family conflict on cognitive aspects of subjective well-being in single parents by 22.6% (R=.266. R2=.218), negative effect of work-family conflict on positive affect of subjective well. -being in single parent is 18.1% (R=.181. R2=.173) and there is a positive effect of work-family conflict on negative affect in single parent by 21.8% (R=.218. R2=.210 ). Abstrak. Adanya konflik yang dirasakan oleh single parent terjadi karena mereka bertanggung jawab sendiri untuk memenuhi tuntutan peran di dalam pekerjaan dan keluarga secara sekaligus, yang biasanya dijalankan berdua oleh suami dan istri sehingga single parent yang bekerja rentan untuk mengalami work-family conflict dan akan berdampak pada subjective well-being nya. Penelitian ini bertujuan untuk mengetahui pengaruh work-family conflict terhadap subjective well-being pada single parent di Kota Bandung. Penelitian ini merupakan penelitian kuantitatif non-eksperimental. Subjek dalam penelitian ini adalah 100 orang single parent yang bekerja di Kota Bandung. Analisis data menggunakan Partial Least Square – Structural Equation Modelling (PLS SEM). Alat ukur yang digunakan untuk work-family conflict adalah work-family conflict scale dari Carlson, Kacmar, & William (2000) yang telah diadaptasi dan diterjemahkan oleh Indah Soca Kuntari, M.Psi, Psikolog (2015). Alat ukur yang digunakan untuk subjective well-being terdiri dari dua alat ukur yaitu, SWLS yang disusun oleh Diener, Emmons, Larsen & Griffin (1985) dan SPANE yang disusun oleh Ed Diener (2009), kedua alat ukur tersebut telah diadaptasi dan diterjemahkan oleh Ratri (2019). Hasil penelitian menunjukan bahwa ada pengaruh negatif dari work-family conflict terhadap aspek kognitif subjective well-being pada single parent sebesar 22,6 % (R=.266. R2=.218), pengaruh negatif work-family conflict terhadap afek positif subjective well-being pada single parent sebesar 18,1% (R=.181. R2=.173) dan ada pengaruh positif work-family conflict terhadap afek negatif pada single parent sebesar 21,8% (R=.218. R2=.210).